Isomorphism Theorems for τ-Semigroups and Ordered τ-Semigroups: Ronnason Chinram, Kittisak Tinpun - Team, Support (Thai Journal of Mathematics, 2009)
The notion of τ-semigroups has been introduced by M. K. Sen and N. K. Saha. τ-semigroups generalize semigroups. Many classical notions of semigroups have been extended to τ-semigroups. Ordered τ-semigroups have been studied by some authors. In this paper, we investigate first and third isomorphism theorems for τ-semigroups and ordered τ-semigroups.